(untitled) (Academic Journal of Internal Affairs, 2011)
Emphasizing the importance of private criminal charges, the author describes a peculiar and controversial homicide investigation, where both suspects confessed to having visited the victim’s apartment, but blamed the other for the crime. For these reasons, the prosecution dropped charges.